Review of the Latest Therapeutic Approaches in the Management of Irritable Bowel Syndrome - Mrozek, Martyna; Blecharczyk, Małgorzata; Jakubiec, Paweł; Kosiński, Maciej; Nowik, Alicja; Pacanowska, Martyna; Sękulski, Marcin; Zydlewski, Igor (Quality in Sport, 2025)
Irritable bowel syndrome (IBS) is a common and chronic bowel disease which, although it does not lead to severe and permanent complications, significantly deteriorates patients’ quality of life. It constitutes a considerable psychological burden for them and also represents a significant socio-economic problem for the healthcare system. Although the cause of the disease is complex and still not fully understood, the update of the Rome criteria has led to significant progress in understanding the pathophysiology of the disease and researching alternative treatment methods. As a result, modern therapeutic approaches can be better tailored to the predominant symptoms and individual needs of the patient. This review compiles the latest research findings on the etiopathogenesis of the disease and discusses available therapeutic strategies, including options unavailable in Poland. This enables a better selection of effective therapy and achievement of satisfactory treatment outcomes through a more individualized approach, tailored to the patient’s specific clinical profile.